Skullcapflavone II suppresses TGF-β-induced corneal epithelial mesenchymal transition in vitro - Meng-Xi Li; Zhen Zhang; Yue Zhang; Fan-Ru Zhao; Yu-Fan Li; Yu-Fei Dang; Yang-Yang Yue; Li Li (International Journal of Ophthalmology)
AIM: To investigate the effect of skullcapflavone II (SCF-II) on the epithelial-mesenchymal transition (EMT) induced by transforming growth factor beta (TGF-β) in human corneal epithelial cells (HCECs), as well as to identify the signaling pathways that may be involved. METHODS: HCECs were cultured in vitro. At a SCF-II (5, 10 µmol/L) dose, cell viability was analysed with a cell counting kit-8 (CCK-8) assay, and cell migration was monitored with wound healing and Transwell migration assays. There were 4 groups: SCF-II, TGF-β, SCF-II+TGF-β and Control. Western blotting and immunofluorescence were performed to show the expression of EMT markers and the translocation of nuclear factor kappa-B (NF-κB) into the nucleus in the 4 groups. RESULTS: Treatment with SCF-II decreased HCEC viability in a dose-dependent manner. A concentration below 10 µmol/L did not present obvious cell toxicity, and survival rates were more than 70% at 48h. Treatment with SCF-II (5 and 10 µmol/L) significantly impeded migration in wound healing and Transwell migration assays (P<0.05), and EMT markers and NF-κB translocation into the nucleus were inhibited. After both TGF-β and SCF-II treatment, the migration of TGF-β-treated HCECs were suppressed by SCF-II (P<0.05). The expression levels of the mesenchymal markers N-cadherin (P<0.05), α-smooth muscle actin (α-SMA; P<0.05) and NF-κB (P<0.05) in both TGF-β- and SCF-II-treated HCECs were lower than those in the HCECs treated with TGF-β alone and higher than those in HCECs treated with SCF-II alone. Immunofluorescence showed that the entry of NF-κB into the nucleus in both TGF-β- and SCF-II-treated HCECs was less than that in the TGF-β-treated HCECs. CONCLUSION: SCF-II inhibit TGF-β-induced EMT in HCECs by potentially regulating the NF-κB signalling pathway. Thus, SCF-II represents a candidate putative therapeutic agent in corneal fibrotic diseases.